Successful percutaneous coronary intervention for chronic total occlusion via the radial artery - Mustafa Adem Tatlisu (İstanbul Kuzey Klinikleri, 2018)
Over the past decade, percutaneous coronary interventions (PCIs) performed via radial artery (RA) access have become popular among interventional cardiologists. Since the radial approach may limit the options in complex cases, most interventional cardiologists prefer femoral access to RA access for complex procedures, such as chronic total occlusions (CTOs) and bifurcation lesions. Presently described is a case of CTO of the right coronary artery that was successfully treated with PCI via the left RA. This study demonstrates that if there is an indication for revascularization and the CTO lesions are short and without poor prognostic factors, an intervention for CTO should still be considered, even if there is no femoral access.